Measurement of residual stress on H13 tool steel during machining for fabrication of FSW/FSP tool pins. (2021) - Butola, Ravi; Choudhary, Naman; Kumar, Ravi; Kumar Mouria, Pradeep; Zubair, Mohammad; Singari, Ranganath M.
Abstract: The development of residual stresses in tools due to machining is a widely known fact and these residual stresses can often lead to unwanted modifications in tool life. Turning, tapering and threading are extensively used in various manufacturing processes and they are specially used for the machining of different types of Friction stir welding/ processing (FSW/FSP) tool pin profiles. FSP being a solid-state process undergoes high levels of plastic deformation and so tool pins having extreme values of residual stresses may pose a problem for longevity of tool life. In this research, turning, tapering, and threading operations were conducted to produce two types of FSW/FSP tool pin profiles namely taper cylindrical and taper threaded. H13 tool steel is extensively used to produce tools FSW/FSP and hence it was chosen. H13 tool steel workpiece with 110 mm length and 22 mm diameter was taken as the workpiece and machining operations were performed to produce FSW/FSP tool on CNC Lathe machine. The objective of the present study is to establish the values of residual stresses developed in both tool pin profiles by utilizing the PulsetecµX-360n portable stress analyzer setup. The results that are achieved are then compared for both the pin profiles – taper cylindrical and taper threaded. It was observed that sigma(x) and tau (xy) residual stresses, both are higher in the case of taper threaded pin, and tau (xy) value is significantly higher for taper threaded.